Environmental Stress: Usaha Mengatasi Stress yang Bersumber dari Lingkungan - Antonius Atosökhi Gea (Humaniora, 2011)
There are times where human relationships with the surrounding environment takes place in a state of balance, so as not to cause pressure against him for human life. But there is also time to balance the relationship is disturbed by various events that often exceed the limits of human adaptability. This last condition arises either by events beyond human control, such as natural disasters or events that arise as a result of human engagement itself, such as over-exploitation of nature and creation of various technology products. The events that happened outside the human self has become a source of stress, which is sometimes understood as external conditions that suppress human adaptation and demanding, and sometimes also understood as a human response to external conditions, which showed special signs, either on the physical, psychological as well as on the visible behavior. Faced with the events that potentially lead to stress, humans need to do assessments leading to a positive attitude toward the stimulus. In addition it should also be developed in ways that help to achieve the adaptation that produces a good balance and lower levels of stress itself. Better anticipation can also be reached in which humans make important changes, mainly related to the views and treatment of the natural environment, and attitudes in developing and utilizing technology, especially related to the negative impacts caused.